Percoco, A Passion For The Past - Creative Teaching Of U.S. History - Cantu, D. Antonio (Teaching History: A Journal of Methods, 2000)
One of the problems facing history/social studies methods instructors is the difficulty in finding a relevant text for use in their courses. While there are numerous methods texts available, few if any are written by and/or from the perspective of the classroom teacher. Those methods teachers who have encountered this same situation will find James A. Percoco’s book to be a great substitute for the clinical secondary social studies textbooks currently on the market.